Diversity, Abundance, and Habitat Association of Medium and Large-Sized Mammals in Tiski Waterfall, Awi Zone, Ethiopia - Derebe, Binega; Derebe, Yonas; Kassaye, Melkamu (International Journal of Zoology, 2022)
The reliable data on faunal diversity, abundance, and habitat preference are essential for proposing and establishing relevant conservation interventions. A survey was done from September 2019 to March 2021 to investigate the diversity, relative abundance, and habitat association of large and medium mammals in Tiski Waterfall, Ethiopia. Data were collected using the line transect survey method in both habitat types. In cliff sites, the point transect was also used. The habitats were populated by large and medium animal species that favor dense forest and shrubland habitats near water sources. During the research, three different habitat categories were evaluated (dense forest, shrubland, and cliff sites). Ten mammalian species were discovered. During the wet season, there were 243 ± 6.6 populations recorded, while during the dry season, there were 204 ± 6.8. Seasonal differences in species abundance were statistically significant p≤0.001. The total populations of the three habitat types were 198.2 ± 7.39, 135 ± 5.35, and 114 ± 5.16 for dense forest, shrubland, and cliff site, respectively. All three habitat categories had a great difference in species abundance p≤0.001. The olive baboon (Papio anubis) was the most common, accounting for 38 percent of the population, followed by the vervet monkey (Cercopithecus aethiops), which accounted for 23 percent. Leopard (Panthera pardus) and common bushbuck (Tragelaphus scriptus) contributed the least to the total, accounting for only 2% each of the total. The highest diversity of mammalian species was found in dense forest (H′ = 0.98), followed by shrubland (H′ = 0.90), and the cliff location has the lowest diversity (H′ = 0.57). The maximum uniformity of the species was found in dense forests (J = 0.51), followed by a shrub region (J = 0.43), and the remaining of the habitat (J = 0.35). Dense forest and shrubland had the highest species similarity (Sl = 0.67), followed by shrubland and cliff site (SI = 0.61). In dense forests with cliff sites, the similarity was lowest (SI = 0.31) in each. To limit the impact of agricultural growth on big and medium mammals, good habitat management is required.